Analysis of Profitability and Resource Management at the Level of Three European Motor Vehicle Manufacturers - Bogdan Cosmin GOMOI (CECCAR Business Review)

(untitled)
The motor vehicle manufacturing sector represents an essential component of a country’s industry. The exponential growth of the parameters provided to customers by manufacturing countries have determined more and more countries to be concerned about implementing such a branch of the productive sector. In addition to the physical wear and tear that the end products of this field are subject to, moral wear and tear becomes increasingly significant. The companies’ added value directly impacts the national GDP, which ultimately represents a combination of added values in a financial year. Profitability and resource management rely equally on financial and accounting information correlated with financial position and performance. A satisfactory profitability and an effective resource management are related to a substantial added value. This paper focuses on analyzing three solid companies operating in this sector, from three European countries with a strong tradition in motor vehicle manufacturing: Renault, from France, Volkswagen, from Germany, and Stellantis, from Italy. Covering the pandemic and post-pandemic period of 2020-2023, the profitability and resource management of these three companies will be comparatively analyzed, as elements directly related to the added value generated by their activity and, by extension, as factors influencing the GDP of the three countries.